Determinant of Behavior of Contraception Selection in Early Marriage Young Mother - Meidina Dewati; Tiyas Kusumaningrum; Retnayu Pradanie (Universitas Airlangga, 2020)
Introduction: Early marriage is a serious problem in Indonesia. It is the beginning of reproductive health problems. This study aimed to explain the factors related to contraceptive selection behavior in young mothers who married early in Surabaya.Methods: Descriptive correlative with Cross-Sectional approach. The independent variables were attitudes, subjective norms, and perceptions of behavioral control, dependents were the intention, and contraceptive selection behavior. The population was young mothers (<20 years) who married early in Kecamatan Semampir and Tambaksari Surabaya. The total sample was 102 respondents. The inclusion criteria were young mothers (<20 years), well verbal communicated and writing, and live with their husbands. Data were collected using a modified questionnaire from Ajzen Theory and analyzed using statistical tests Spearman's rho with significance level ≤ 0.05.Results: Result showed that (p = 0.000 r ≥ 0.650) Ajzen theory correlate with the intention to choose contraception and intention towards contraceptive selection behavior.Conclusion: The more positive the attitude, the better the intention of using contraception. Subjective norms and perceptions of good behavior control lead to good intentions in choosing contraception. Good intentions lead to good behavior in using contraception. It is expected that young mothers who married early with a positive attitude, subjective norms, perceptions of behavioral control, and good intentions can have a positive influence on the other young mothers by sharing insights and experiences regarding contraception.